Hybridity in Joshua Whitehead’s Full Metal Indigiqueer - Heather Milne (Humanities)
This essay reads Oji-Cree poet Joshua Whitehead’s full metal indigiqueer in relation to hybridity. Whitehead’s poems are both lyrical and experimental, offering a hybrid poetics that resonates with existing critical discussions of hybridity, but he also extends hybrid poetics in new directions through his engagement with posthuman and Indigenous futurism and through his development of Zoa, the hybridized trickster figure who combines the technological and the biological, who features so prominently throughout the collection. Indigiqueerness emerges in these poems as a hybrid identity positioned not only to survive but to thrive in the twenty-first century and beyond.